Academic Administration in the Artificial Intelligence Era of School Administrators Under Bang Khun Thian District Office in Bangkok Metropolis - Yottawan, Kitiporn; Panjarattanakorn, Darunee (Journal of Graduate MCU KhonKaen Campus, 2025)
The objectives of this study were 1) to examine the academic administration in the artificial intelligence era of school administrators under Bang Khun Thian District Office Bangkok in Bangkok Metropolis, and 2) to compare teachers’ opinions on academic administration classified by gender, age, educational level, work experience, and school size. The sample consisted of 296 teachers selected through stratified random sampling based on school size. The research instrument was a questionnaire with content validity ranging from .67 to 1.00 and a reliability coefficient of .99. Data were analyzed using frequency, percentage, mean, standard deviation, t-test, one-way ANOVA, and LSD post hoc test. The research findings revealed that: 1) overall academic administration was rated at a high level. Ranked from highest to lowest were instructional management, development and utilization of educational media and technology, educational supervision, assessment, evaluation, academic credit transfer, and curriculum development. 2) There were no statistically significant differences in teachers' overall opinions when classified by age, work experience, gender, educational level, or school size. However, statistically significant differences were found in specific areas: curriculum development by gender (p < .05), assessment evaluation and academic credit transfer and educational supervision by educational level (p < .05), and instructional management by school size (p < .05).